Technical and economic efficiency of Russian corporate farms: the case of the Moscow region; Determinatnten der technischen und ökonomischen Effizienz von landwirtschaftlichen Betrieben in Russland: Der Oblast Moskau - Nikolai Svetlov; Heinrich Hockmann (Institute of Agricultural Development in Central and Eastern Europe (IAMO), 2005)
The research focus of the paper is to distinguish allocative and technical inefficiencies on Moscow region corporate farms. DEA specifications with both monetary and technical objective functions are applied. Reduced costs and sensitivity analyses are used to identify fixed inputs constraining either allocative or technical efficiency. To decrease heterogeneity and allow for the accessibility to different technologies of a given farm, the farms are grouped with respect to the set of outputs they produce. Thus, as a result of an unstable market environment, it is shown that allocative inefficiency causes 65-100 % (depending on the group) of total inefficiency in 2002 and 60-96 % in 1999. As for technical inefficiency, in 1999 its major source was the lack of liquidity (30-48 %) and other resources; in 2002 it was the lack of fodder (up to 37 %), liquidity (up to 31 %) and sown area (48 % in one of the groups). The role of insufficient management in regional farming inefficiency is evaluated as being much lower than many earlier studies suggest. – – In dem Diskussionspapier wird eine Unterscheidung zwischen allokativer und technischer Effizienz landwirtschaftlicher Betriebe in der Region Moskau vorgenommen. Hierzu werden DEA-Modelle mit technischen und ökonomischen Zielfunktionen spezifiziert. Mit Hilfe von Sensitivitätsanalysen werden Inputs identifiziert, die zu allokativer und technischer Ineffizienz führen. Um die Heterogenität in der Stichprobe zu reduzieren und um die Verfügbarkeit von Technologien für die landwirtschaftlichen Betriebe besser abbilden zu können, werden die Unternehmen entsprechend ihrer Produktionsstruktur gruppiert. Die Ergebnisse zeigen, dass je nach Gruppen die allokative Ineffizienz in den Jahren 1999 und 2002 zwischen 60 und 100 % der gesamten Ineffizienz erklärt. Dies deutet darauf hin, dass das unzureichende Management von größerer Bedeutung ist, als frühere Studien vermuten lassen. Die Hauptursache für die technische Ineffizienz war 1999 das Fehlen liquider Mittel. Im Jahr 2002 waren neben der Liquidität, die Verfügbarkeit von Futtermitteln und die Saatfläche die Inputs, die für die Ineffizienz verantwortlich waren. Der Anteil der bindenden Restriktionen betrug in den einzelnen Gruppen bis zu 31 %, 37 % und 48 % bei den genannten Faktoren.
urn:nbn:de:gbv:3:2-5623
Keywords: D24; Q12; C14; 330; Technical inefficiency; allocative inefficiency; Data Envelopment Analysis; Moscow region; transitional economy; Technische Ineffizienz; Allokative Ineffizienz; Data Envelopment Analysis; Region Moskau; Transformationsländer